2020
DOI: 10.1021/acsami.0c19074
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Regenerable Cerium Oxide Nanozyme-Loaded pH/H2O2-Responsive Nanovesicle for Tumor-Targeted Photothermal and Photodynamic Therapies

Abstract: Photodynamic therapy (PDT) and photothermal therapies (PTTs) are both promising strategies for effective tumor therapy. However, the absence of O 2 at tumor sites hinders the sustained response of photosensitizers. Here, we develop a recycled cerium oxide (CeO 2 ) catalase nanozyme-loaded hyaluronic acid nanovesicle to address the hypoxic tumor microenvironments and targeted delivery of the photosensitizers [indocyanine green (ICG)] to tumors. A polysaccharide complex effectively modifies the surface of a poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 40 publications
0
47
0
Order By: Relevance
“…Due to the lack of high selectivity and specificity, the aggregation effect of nanocarriers without active targeting on tumor tissues is low [ 11 14 ]. Therefore, nanocarriers with specific modifications that enable binding to tumor cell surface receptors or antigens are desirable for site-specific targeting [ 15 18 ]. The hydrophobic and electrical properties of these targeted groups on nanocarriers may reduce their time in circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of high selectivity and specificity, the aggregation effect of nanocarriers without active targeting on tumor tissues is low [ 11 14 ]. Therefore, nanocarriers with specific modifications that enable binding to tumor cell surface receptors or antigens are desirable for site-specific targeting [ 15 18 ]. The hydrophobic and electrical properties of these targeted groups on nanocarriers may reduce their time in circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Given their antioxidation properties, cerium oxide NPs may be used to deliver oxygen to tumor regions. Indeed, it was shown that cerium oxide NPs generate O 2 inside tumors by consuming endogenous H 2 O 2 (Yao et al, 2018;Liu et al, 2020;Zeng et al, 2020). For example, Yao et al (2018) reported that a synergetic mesoporous cerium oxide upconversion nanoparticle (Ce-UCNP; Figure 3 to trigger cellular apoptosis.…”
Section: Cerium-based Nanomaterialsmentioning
confidence: 99%
“…For instance, the concentration of hydrogen peroxide in tumor cells is reported to be approximately 10 μM, which is higher than normal cells. Boronic acid esters are typical hydrogen peroxide-responsive moieties ( Saravanakumar et al, 2017 ; Zeng et al, 2020 ). In addition, GSH is abundant in a tumor intracellular environment (2–10 mM) ( Li and Yan, 2018 ).…”
Section: Smart Polymeric Delivery System For Antitumor Photodynamic Therapymentioning
confidence: 99%
“…Based on the different microenvironments of tumor and normal tissues, a variety of activatable polymeric delivery systems are emerging ( Park et al, 2016 ; Sun et al, 2017 ; Wei et al, 2018 ; Li et al, 2019c ; Yan et al, 2020 ; Zeng et al, 2020 ; Yang et al, 2021 ). Despite the different structures and constituents of thousands of reports, they mainly achieve the activation via the following three strategies: (1) self-quenching and dequenching of photosensitizers due to aggregation and disintegration; (2) utilize another quencher to quench the triplet state of photosensitizer and dequenching upon cleavage of sensitive bonds; and (3) the change of size and surface charge to induce an enhanced internalization by tumor cells.…”
Section: Smart Polymeric Delivery System For Antitumor Photodynamic Therapymentioning
confidence: 99%